Assessing the reproductive biology of the Greenland shark (Somniosus microcephalus) - Nielsen, Julius; Hedeholm, Rasmus B.; Lynghammar, Arve; McClusky, Leon Mendel; Berland, Bjørn; Steffensen, John Fleng; Christiansen, Jørgen Schou (PLOS ONE, 2020)
The Greenland shark ( Somniosus microcephalus , Squaliformes: Somniosidae) is a long-lived Arctic top predator, which in combination with the high historical and modern fishing pressures, has made it subject to increased scientific focus in recent years. Key aspects of reproduction are not well known as exemplified by sparse and contradictory information e.g. on birth size and number of pups per pregnancy. This study represents the first comprehensive work on Greenland shark reproductive biology based on data from 312 specimens collected over the past 60 years. We provide guidelines quantifying reproductive parameters to assess specific maturation stages, as well as calculate body length-at-maturity (TL 50 ) which was 2.84±0.06 m for males and 4.19±0.04 m for females. From the available information on the ovarian fecundity of Greenland sharks as well as a meta-analysis of Squaliform reproductive parameters, we estimate up to 200–324 pups per pregnancy (depending on maternal size) with a body length-at-birth of 35–45 cm. These estimates remain to be verified by future observations from gravid Greenland sharks.